'I don't know what I am doing!': Surfacing struggles of managerial identity work. Issue 5 (November 2014) - Hay, Amanda
Recent work contends that management education provides an important space for managers' identity work. However, it is also recognised that much of what is currently offered constrains rather than enables managers' identity work. Against this background, I present material which provides important practical possibilities to managers for more realistic and helpful forms of identity work, and theoretically, also add to the development of a more nuanced understanding of managerial identity work processes. Drawing on interviews with a range of managers, I offer rare empirical evidence, which illustrates the ordinarily suppressed emotional struggles of the mismatch between social identities of manager and self-identities. In this way, I contribute to current theoretical offerings to demonstrate the centrality of emotions to processes of becoming. In turn, I propose that exploration of these emotions offers management educators important possibilities for facilitating managers' identity work.